Internet of Things-Based Automation System for Watering Cayenne Pepper Plants - Akbar, Reza Maulana; Maulindar, Joni; Muhammad, Nibras Faiq (Journal of Artificial Intelligence and Software Engineering, 2025)
This study aims to build an Internet of Things (IoT)-based automatic watering system intended for cayenne pepper farmers in rural areas. The system is designed to irrigate plants automatically based on environmental parameters obtained in real-time. The hardware components consist of an ESP32 microcontroller, a DHT22 temperature and humidity sensor, a soil moisture sensor, a relay module, and a DC water pump. Sensor data are processed by the ESP32 and transmitted to a Supabase database using the HTTP protocol, then visualized through a local web-based interface. Testing results show that the system functions automatically and responsively when the soil moisture value falls below the predetermined threshold. The monitoring interface displays real-time temperature, soil moisture, and a history of recent watering activities. This system is considered effective in reducing labor and optimizing water usage, while also providing a digital solution that aligns with small-scale precision agriculture practices. Based on the results, the system is deemed feasible for implementation and further development.